Online Identification of Aircraft Model Parameters Based on Recursive Least Squares Method - JIANG Yongming; WANG Changqing; XU Cheng (Kongzhi Yu Xinxi Jishu)
In order to realize online update of the flight control system, online assessment of flight capability and online detection of an aircraft fault, the online identification method of unknown parameters in the aircraft dynamics model was studied. Firstly, based on the analysis of aircraft characteristics, the longitudinal small disturbance linear motion equation and the longitudinal nonlinear motion equation are selected as the identification model. Then, the recursive least squares method is used to identify the parameters of the Single Input and Multiple Output (SISO) linear motion model and the linear subsystem of the multiple input and multiple output (MIMO) nonlinear motion model. The simulation results show that the recursive least squares method has fast convergence speed and high computational efficiency. The identification accuracy meets the engineering requirements and can be used for online identification. However, this method is only suitable for simple linear models and cannot be directly adopted for nonlinear complex motion models.